2 answers:
Answer:
3. 6
Step-by-step explanation:
X - y = 4 ( Equation 1 )
X + y =8 ( Equation 2 )
equation 1 + equation 2
; 2x = 12
x = 12÷2
x =6
hope it helps ☺️
Answer: n=6
Step-by-step explanation:
You might be interested in
Here’s the answer hope it helps
It is 3 cause they are all the same leatheth so 3
The answer is 50,51 and 52
Answer:
2.33 yards
Step-by-step explanation:
3 1/2-3.5
2/3-0.66
0.66 x 3.5 = n
![y = {(x + 1)}^{2} - 1](https://tex.z-dn.net/?f=y%20%3D%20%20%7B%28x%20%20%2B%201%29%7D%5E%7B2%7D%20%20-%201)
The one is a vertical translation of the parent function to the left of one
![f(x) = {x}^{2}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%20%7Bx%7D%5E%7B2%7D%20)
making it -1.